The Effect of Online Game Intensity on Social Interaction on Adult Users - Arini Bunga Firdaus; Ahmad Labiq (Jurnal Neo Konseling, 2021)
Online games are an activity that has become a habit for teenagers and even adults, with thishe purpose of this study is to determine the existence of technology that is able to change the pattern of human interaction and the reasons behind the use of technology in the process of social interaction. The object of this research is adolescents who enter the adult phase. This type of research uses qualitative methods with observations and interviews, data sourced from primary data with questionnaires or questionnaires. Based on the results of the study, the use of online games tends to reach the adult phase. Thus, adolescents need to be given efforts to prevent addiction to online games, so that they are expected to avoid addiction to online games. It is also hoped that related parties can synergize in carrying out the various efforts that have been submitted. This will have a negative impact on various aspects of teenagers' lives.